2021
DOI: 10.3389/fonc.2021.796555
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Aging-Related Gene Signature in Predicting Prognosis and Indicating Tumor Immune Microenvironment in Breast Cancer

Abstract: Breast cancer (BC) is the most commonly diagnosed malignancy accompanied by high invasion and metastasis features. Importantly, emerging studies have supported that aging is a key clue that participates in the immune state and development of BC. Nevertheless, there are no studies concerning the aging-related genes (AGs) in constructing the prognosis signature of BC. Here, to address this issue, we initially performed a systematic investigation of the associations between AGs and BC prognosis and accordingly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The ARGs that overlap our prognostic model with its model are PLAU and TOP2A. In addition, PLAU has predictive value as ARG in breast cancer, lung square cancer, head and neck square cell cancer, etc (Yang et al, 2020;Lv et al, 2021;Zhai et al, 2022). TOP2A can predict the prognosis of hepatocellular carcinoma (Cai et al, 2022).…”
Section: Figure 12mentioning
confidence: 99%
“…The ARGs that overlap our prognostic model with its model are PLAU and TOP2A. In addition, PLAU has predictive value as ARG in breast cancer, lung square cancer, head and neck square cell cancer, etc (Yang et al, 2020;Lv et al, 2021;Zhai et al, 2022). TOP2A can predict the prognosis of hepatocellular carcinoma (Cai et al, 2022).…”
Section: Figure 12mentioning
confidence: 99%
“…Therefore, exploring prognostic signature of ARG is vital to understand the function of aging process in BC. There are currently two studies similar to ours, 14 , 15 The difference in method was that the ARGs we used to construct the signature were associated with survival overlapped both in the TCGA training set and the GEO validation set, and this method was the most accurate and convincing, while the other two study was only used the TCGA training set to construct the signature which were differed from the method of our study. And our study closely linked prognostic signature to immune, clinical treatment (including chemotherapy, immunotherapy, and targeted therapy) to elaborate the associations with clincal traits, the other two studies were not sufficiently linked to clinical treatment.…”
Section: Discussionmentioning
confidence: 83%
“…Aging is an independent risk factor for some cancers [24]. In addition, aging-related markers have prognostic potential for predicting cancer [27]. The above facts indicated that we urgently need to identify more aging-related molecular markers in BC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, some aging-related molecular markers that can predict invasive BC have been verified [27], but the utilization of aging-related lncRNAs in BRCA has not been presented. We utilized many samples in the TCGA and GEO databases to identify and validate the risk model, which can predict the survival, pathological characteristics, and treatment methods of BC patients well, thereby providing powerful guidance for clinical practice.…”
Section: Discussionmentioning
confidence: 99%